Subway Station and Neighborhood Crime: an Egohood Analysis Using Subway Ridership and Crime Data in New York City - Li, Nan (Crime & delinquency, 2023)
In the current study, we examine the effects of the number of subway stations as well as magnitude of subway ridership on crime in 1/4-mile egohoods in New York City, while accounting for structural characteristics and land uses. Longitudinal analyses are conducted using a set of negative binomial regression fixed effects models. We found that the number of subway stations have crime-enhancing effects for robbery, aggravated assault, burglary, and larceny, but crime-reducing for motor vehicle theft. We found mixed findings for subway ridership across different crime types. We also found that the effects of subway stations are moderated by the proportion of retail land use in place. The findings provide evidence that subway stations and ridership have important consequences for the spatial patterns of crime.